Chemical Intolerance and Mast Cell Activation: A Suspicious Synchronicity - Raymond F. Palmer; Tania T. Dempsey; Lawrence B. Afrin (MDPI AG, 2023)
Background: Chemical Intolerance (CI) is characterized by intolerances for chemicals, foods, and drugs with multi-system symptoms. As yet, the biomechanism remains unclear. One study reported converging lines of evidence supporting a substantive association between mast cell activation syndrome (MCAS) and CI. The purpose of this study is to (1) confirm a previous report demonstrating that 60% of MCAS patients report CI and (2) examine the parallels between symptoms and intolerances in CI and MCAS. Methods: Five hundred forty-four MCAS patients were assigned a clinical MCAS score using a validated assessment instrument and were assessed for CI using the validated Quick Environmental Exposure Sensitivity Index. Results: Our outcomes confirm the previously published study where the majority of MCAS patients also have CI. There was a clear overlap between various ICD-10 diagnostic categories and CI symptoms, providing further support for a potential shared mechanism. Conclusions: Exposures to pesticides, volatile organic compounds, combustion products, and mold have previously been reported as initiators of CI. However, until recently, little was known about the biological mechanism involved that could explain the multisystem symptoms associated with CI. This paper addresses a newly identified biomechanism for disease, which may underlie a host of "medically unexplained symptoms" triggered by xenobiotics.